Protein based biomaterials for therapeutic and diagnostic applications. (26th October 2021) - Chu, Stanley; Wang, Andrew L; Bhattacharya, Aparajita; Montclare, Jin Kim
Abstract: Proteins are some of the most versatile and studied macromolecules with extensive biomedical applications. The natural and biological origin of proteins offer such materials several advantages over their synthetic counterparts, such as innate bioactivity, recognition by cells and reduced immunogenic potential. Furthermore, proteins can be easily functionalized by altering their primary amino acid sequence and can often be further self-assembled into higher order structures either spontaneously or under specific environmental conditions. This review will feature the recent advances in protein-based biomaterials in the delivery of therapeutic cargo such as small molecules, genetic material, proteins, and cells. First, we will discuss the ways in which secondary structural motifs, the building blocks of more complex proteins, have unique properties that enable them to be useful for therapeutic delivery. Next, supramolecular assemblies, such as fibers, nanoparticles, and hydrogels, made from these building blocks that are engineered to behave in a cohesive manner, are discussed. Finally, we will cover additional modifications to protein materials that impart environmental responsiveness to materials. This includes the emerging field of protein molecular robots, and relatedly, protein-based theranostic materials that combine therapeutic potential with modern imaging modalities, including near-infrared fluorescence spectroscopy, single-photon emission computed tomography/computed tomography, positron emission tomography, magnetic resonance imaging, and ultrasound/photoacoustic imaging.